Strategi Penyusunan Soal High Order Thinking Skills (HOTS) utuk Guru Sekolah Dasar - Ari Irawan; Chatarina Febriyanti; Gita Kencanawaty (Universitas Indraprasta PGRI, 2026)
The purpose of this community service is to improve teachers' competence in developing HOTS-based test questions. HOTS itself is not synonymous with difficult questions, but rather questions that can train students' reasoning, critical thinking, and creativity. The community service was carried out in three stages: preparation, implementation, and evaluation. The preparation phase involved obtaining permits and coordinating with relevant parties regarding the activities to be conducted. The implementation phase involved collaborating with school principals and teachers to conduct workshops, question-and-answer sessions, and simulations related to the development of HOTS-based questions. The results obtained are: 1) Teachers understand that HOTS questions are not synonymous with difficult questions. 2) Teachers can use operational terms C4, C5, and C6 in Bloom's Taxonomy. 3) Teachers can create HOTS questions appropriate to students' ability levels in line with differentiated learning in the Merdeka Curriculum